Hexachlorocyclohexane (HCH): Optimization of Mechanochemical Degradation Process by CaO - Pelitli, Volkan; Kurt, Ugur (GAZI UNIV, 2021)
Although the use of hexachlorocyclohexane (HCH,C6H6Cl6) as the pesticide for agricultural purposes is now prohibited in many countries because of its hazardousness, stockpiles of HCH still available today. At this point mechanochemical degradation (MCD) has a remarkable potential for the environmental disposal of some HCH isomers. But the mechanism still needs to be further researched and optimized for better reaction conditions to achieve satisfactory degradation of dominant HCH isomers (alpha-, beta-, gamma-, and delta-HCH) together with the reduction of energy consumption and increasing the dechlorination efficiency. While all the previous studies have revealed the effects of operating conditions such as rotational speed, ball size and mass ratios individually, interactions between general parameters have not been determined yet. In the present work, relationships between parameters were investigated, for the first time, using response surface statistical model (RSM) with Box-Behnken Design (BBD) and the operating parameters interactions were optimized on the degradation efficiency of MCD with calcium oxide (CaO) which provides electrons to HCH isomers by planetary ball mill. The experimental results indicated that the best degradation efficiency (%100) was achieved after 480 min. grinding at a charge ratio 1/20 (0,05) HCH/CaO with 1/5 (0,2) mixture/ball mass ratio and a mill rotation speed of 700 rpm. Based on these results, optimization of operating parameters allowed the degradation of dominant HCH isomers effectively and in fast manner. These approaches may also be beneficial for ex situ disposing of other persistent organic pollutants (POPs) by MCD.
Keywords: Hexachlorocyclohexane (HCH); mechanochemical degradation (MCD); persistent organic pollutants (POPs); FLY-ASH; DESTRUCTION; BALL; DECHLORINATION; FE; Engineering